Peran Keterlibatan Pekerjaan sebagai Intervensi Efikasi Diri dan Komitmen Profesional - Nancy Yusnita (Asosiasi Ahli Administrasi Indonesia, 2020)
Many of research on professional commitment had generated findings that professional commitment is considered to predict individual performance. The objective of this study is to examine factors that have an effect to professional commitment namely selfefficacy and job involvement. Respondents consisted of lecturers at 4 different private universities in the city of Bogor, Indonesia. The sample for the study consisted of 252 permanent lecturers derived randomly from its population. The study mainly utilized quantitative data (from questionnaires). Regression and correlational analysis were used to find out the relationship among variables. In general, this study aims to find efforts that can be made to increase professional commitment. The results showed that there was a positive effect of self-efficacy and job involvement on professional commitment, there was a positive effect of self-efficacy to job involvement, and there was a positive effect of selfefficacy to professional commitment through job involvement.